ASSOCIATION OF FIBROTIC CHANGES IN LIVER ON FIBRO-SCAN WITH VIRAL LOAD IN HEPATITIS C POSITIVE PATIENTS - A PILOT SUDY - Arshad, Muhammad; Iqra Manzoor,; Khalid Hussain Memon,; Asif Haider,; Umer Aziz Khan,; Iraj Nayab,; Zareen Fatima, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Hepatitis C is a diverse illness that causes significant death and morbidity. The hepatitis C virus infects hundreds of millions of individuals globally (HCV). More than 80% of those infected develop chronic infection; the remaining 10-20% recover spontaneously through natural immunity. Acute hepatitis is only icteric in 20% of individuals and is seldom severe. Methods: A pilot study was conducted at INOR hospital Abbottabad. Eleven hepatitis C positive and 10 hepatitis C negative participants were included in the study. Results: A significant difference correlation was found between viral load and SWE quantification for fibrosis stage in Kilo-Pascal, r= 0.904 (p-value=0.000 <a=0.05). HCV positive patients showed a viral load of (Mean±SD) 128,185.8±153,719.1. Conclusion: Although a biopsy is considered to be gold standard for determining the degree of damage caused by chronic viral hepatitis, it is far from perfect. Liver elastography is an intriguing technique that can help physicians make difficult decisions while treating viral hepatitis. This study showed that fibrotic changes of liver are directly proportional to the presence of viral load in blood. The greater the viral load more severe fibrosis will be seen. Age also plays a role in severity of fibrosis, however, more studies on larger population is required to support this statement.